Constructionist Studies of Social Problems: How We Got Here, and Where We Ought to Go - Best, Joel (SocietàMutamentoPolitica, 2018)
The principal theory of social problems (at least in the United States) is the social constructionist perspective, which defines social problem in terms of a claimsmaking process, rather than as a type of social condition. This perspective emerged in the 1970s, and its spread has led to many hundreds of case studies, both by American scholars and by sociologists in many other countries. While constructionists may be pleased by their perspective’s success, they need to be aware that there are many academic fads. In order to avoid becoming a forgotten intellectual fad, constructionists need encourage several sorts of new contributions: They need to move beyond case studies and concentrate on synthesizing the research that exists; they need to foster the spread of constructionism in many more countries; they need to expand their focus beyond the present with studies of social problems construction in the past and the future; they need to develop clear methodological principles; and they need to foster collaboration with scholars in other disciplines.